Hepatitis c virus RNA quantification using Evagreen® dye real time PCR - Hamzah, Hairul Aini; M. Saleh Habil, Akrahm; Mustafa Mahmoud, Mohammed Imad Al-Deen; A.Talib, Norlelawati; Hasmoni, Mohamed Hadzri (2016)
Background: HCV exhibits extreme genome heterogeneity, additionally it usually present in blood at a low copy number. Thus, high specificity and sensitivity represent a major challenge during development of any HCV detection and quantification assay.. Objective: The aim of the present study was to establish a highly specific and sensitive semi-nested real time PCR using EvaGreen dye for detecting and quantifying HCV RNA. Methodology: This is a laboratory cross-sectional study. A total of 50 serum samples, comprising 40 HCV- positive and 10 HCV-negative, were included in our study. RNA was extracted, reverse transcribed, and then subjected to two rounds of PCR amplification. In the first round, conventional PCR was performed using a pair of primers targeting the 5'UTR. In the second round, real time PCR using EvaGreen dye and primers targeting a region within the previously amplified product was carried out for sensitive detection and quantification. Reference samples with known viral load were treated similarly to the unknown samples and used to create the standard curves. Results: Our method showed a high level of analytical specificity and accuracy, with a low limit of detection (~2 IU/ml). It yielded repeatable results with less than 4% of intra- assay variation. The assay covered a broad dynamic range of quantification, ranging from 0.34 to 6 log IU/ml. The diagnostic sensitivity, specificity, and accuracy were all 100%, indicating neither false positive nor false negative results were obtained. Conclusion: The newly developed semi-nested real time PCR using EvaGreen dye has demonstrated a high analytical and diagnostic performance for HCV viral load, suggesting its potential to have wide applications in clinical diagnosis and therapeutic management. Key words: Hepatitis C, Real-time PCR, viral load